2018
DOI: 10.1002/jcb.27827
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐mediated apoptosis was induced by oleuropein in H1299 cells involving activation of p38 MAP kinase

Abstract: Lung cancer is the main health threat in the world. Recently, oleuropein has been reported to have potent antioxidant and anticancer activities. However, the antitumor effects of oleuropein on H1299 cells are not well understood. Therefore, the purpose of this paper is tantamount to explore the effects of oleuropein on H1299 cells and its underlying mechanism that may be involved. Oleuropein treatment in H1299 cells resulted in cell cycle distribution at G2/M arrest and apoptosis in a dose‐dependent manner. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
(159 reference statements)
5
19
0
Order By: Relevance
“…Apoptosis is programmed cell death that is an important process in the pathogenesis of liver cancer (Goldar, Khaniani, Derakhshan, & Baradaran, ). Some studies have shown that the mitochondrial pathway can initiate and mediate apoptosis via regulation by Bcl‐2 family members, including Bcl‐xl, Bad, and Bax (Wang, Huang, et al, ; Wang, Wu, et al, ). It has been suggested that ISL induces apoptosis via inhibition of the STAT3 signaling pathway, and activating the mitochondrial pathway associated with cleavage of caspase‐3, ‐7, and ‐9, and increased the expression levels of Bax, decreasing the levels of Bcl‐2 and Bcl‐xl in human renal carcinoma Caki cells (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is programmed cell death that is an important process in the pathogenesis of liver cancer (Goldar, Khaniani, Derakhshan, & Baradaran, ). Some studies have shown that the mitochondrial pathway can initiate and mediate apoptosis via regulation by Bcl‐2 family members, including Bcl‐xl, Bad, and Bax (Wang, Huang, et al, ; Wang, Wu, et al, ). It has been suggested that ISL induces apoptosis via inhibition of the STAT3 signaling pathway, and activating the mitochondrial pathway associated with cleavage of caspase‐3, ‐7, and ‐9, and increased the expression levels of Bax, decreasing the levels of Bcl‐2 and Bcl‐xl in human renal carcinoma Caki cells (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, defects in the apoptotic process can cause uncontrolled cell proliferation and tumor formation (Mukherjee, Saviola, & Mackessy, ; Park et al, ). Phosphorylated mitogen‐activated protein kinases (MAPKs) regulate mitochondrial apoptotic pathways, as well as the expression of apoptosis‐related proteins, such as B‐cell lymphoma‐2 (Bcl‐2) family members, causing a cysteine aspartase (caspase) family cascade reaction and eventually inducing apoptosis (Wang, Huang, et al, ; Wang, Wu, et al, ). In addition, reactive oxygen species (ROS) accumulation, as well as signal transducer and activator of transcription 3 (STAT3) and nuclear factor‐kappa B (NF‐κB) pathways, play key roles in regulating apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer effects of Ole were also examined in vitro in human cervical cancer cells (84), PC cells (85), and neuroblastoma cells (86,87) and in vivo in the melanoma mouse model (38,88), with promising results. Two very recent studies demonstrated the beneficial effects of Ole in different types of lung cancers (89,90). The diversity of Ole's anticancer properties renders it a potential natural therapeutic in the future treatment of these malignant diseases.…”
Section: Anticancer Effects Of Htyr Ole Oleacein Ocmentioning
confidence: 99%
“…Cytochrome c (Cyt c), a heme-containing mitochondrial protein, has a critical function in both respiration and apoptosis. During apoptosis, cytochrome is released into the cytosol, where it subsequently participates in the process leading to caspase-9 and caspase-3 activation (35). The current results indicated that miR-182-5p expression was regulated in USMSCs by sufentanil or ropivacaine treatment, and that miR-182-5p improved cell survival and suppressed cell apoptosis by targeting BCL10 and CYCS expression.…”
Section: Discussionmentioning
confidence: 55%